Faktor-Faktor yang Mempengaruhi Penyaluran Kredit pada Bank Umum Periode 2008-2012 - Diana Hasyim (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2014)
This research purposes to understand the direct and indirect impact of ‘Third Party Funds’, ‘Non Performance Loan’, ‘Return On Assets’ and ‘Capital Adequacy Ratio’ to Banking Lending. Population of the research is ‘go public’ commercial bank in Indonesia in which 23 of them taken as sampel of research which were selected purposively based on the assumption that they became ‘go public’ in the period of 2008-2012. Whereas, the data analyzed by path analysis technique, while both ‘t-test’ and ‘correlation test’ were used in testing of hypothesis. Then, the finding shows that both variable of ‘third party funds’ and ‘return on assets’ impact significantly to ‘Capital Adequacy Ratio’. Furthermore, the ‘Third Party Funds’ and ‘return on assets’ impact positively to the Banking Lending, while Non-Performance Loan and Capital Adequacy Ratio impact significant negatively to Banking Lending